Pengaruh Komunikasi Internal dan Kerjasama Tim terhadap Kualitas Kerja Karyawan RSI Mabarrot MWC NU Bungah Gresik - Ahmad Khairul Hakim; Syifaun Nabilah Medika Putri (Journal of Islamic Management, 2022)
This study aims to determine the effect of internal communication and teamwork on the quality of work of employees simultaneously or partially at RSI Mabarrot MWC NU Bungah Gresik. The method used in this research is associative quantitative research. The researcher used multiple linear regression in answering the research objectives. This research is located at RSI Mabarrot MWC NU Bungah Gresik with a total of 87 respondents. The results of this study obtained test results on the formulation of the problem to prove that: First, there is a significant effect on internal communication and teamwork on the quality of employee work simultaneously. The two variables have a p value of 0.000 < 0.05. Second, there is a significant effect on internal communication and teamwork on the quality of employees' work partially. Third, the variable of internal communication and teamwork on the quality of employee work is the r value of 0.771. The value of 0.771 indicates the value of a strong relationship given the independent variable and the dependent variable. This variable has a p value of 0.000. Fourth, internal communication has a correlation value of 0.637, while teamwork has a correlation value of 0.719. Both of these variables indicate that internal communication and teamwork get a high or strong contribution. Fifth, the variable that has the highest value is teamwork, which is 0.719. Sixth, the regression model can be used as a predictor of employee performance in the future. This is due to the SEE value < standard deviation, which is 3.337 < 2.218.